دراسة تحليلية لتطبيق مبادئ الحوكمة في سوق عمان للأوراق المالية - خضير, عقبة; زهواني, رضا; العيفة, رحيمة (جامعة الوادي University of Eloued, 2018)
تناولت هذه الورقة البحثية دراسة تحليلية لتطبيق مبادئ الحوكمة في سوق عمان للأوراق المالية،وذلك من خلال التركيز الاهتمام على مبادئ الحوكمة ومدى تطبيقها في سوق عمان للأوراق المالية،بالإضافة إلى استعراض المفاهيم الأساسية لحوكمة الشركات وكذلك الدور الكبير التي تلعبه الحوكمة في سوق المال، في محاولة إبراز مدى تطبيق مبادئ الحوكمة في هذه السوق حيث وصلنا إلى أن تطبيق مبادئ الحوكمة يعطي قدرا من الطمأنينة والثقة للمستثمرين بالإضافة إلى أنه لم يتم التفصيل في قواعد الحوكمة في سوق عمان بل تم وضع قاعدة عامة ومن ثم ترك التفصيل إلى التشريعات، ويهدف إتباع هذا الأسلوب إلى منح الشركات مرونة في التطبيق ووقتا كافيا للتكيف مع متطلبات قواعد الحوكمة بما يعزز الوعي بهذه القواعد ومن ثم تحقيق الالتزام الكامل بها بشكل متدرج. This paper discusses an analytical study of the application of the principles of governance in the Amman Stock Exchange by focusing attention on the principles of governance and its application in the Amman Stock Exchange, in addition to reviewing the basic concepts of corporate governance as well as the great role played by governance in the capital market. To highlight the extent to which the principles of governance in this market have been applied. We have concluded that the application of the principles of governance provides a measure of confidence and confidence to investors. In addition, the rules of governance in the Amman market have not been elaborated. A method to give companies flexibility in the application and sufficient time to adapt to the rules of corporate governance requirements so as to enhance awareness of these rules and thus achieve their full commitment to progressively.
مقال
Keywords: حوكمة الشركات، سوق عمان للأوراق المالية ، مبادئ الحوكمة ، تماثل المعلومات.; Corporate Governance, Amman Stock Exchange, Principles of Governance, Information Similarity.